WARM-UP IN THE DISCIPLINE OF COMPUTER SPORTS "COMBAT ARENA" - Kosmina E.A.; Makarov Yu.M.; Lutkova N.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to compare various warm-up complexes involved in the discipline of computer sports "combat arena". Methods and structure of the study. The scientific work included two stages. At the first stage, a survey was made of 32 athletes involved in the “combat arena” (Dota 2) of the first or third sports category, according to the results of the survey, 3 sets of exercises for warm-up were compiled. In the second part of the study, 10 young men from 18 to 25 years old took part. The participants of the study were asked to perform a warm-up and play a game match in the rating mode in the chosen form of the program. Immediately after the warm-up, the tone of the muscles of the hand and forearm, the trapezius muscles in a relaxed and tense state, thermography of the fingers and hands, and the level of concentration of attention were measured. Results and conclusions. The revealed relationships between the tone of the relaxed trapezius muscles, delta tone and concentration of attention indicate the expediency of including in the training process those involved in the "combat arena" means aimed at reducing the tone of the trapezius muscles and muscles of the hand and forearm. The greatest efficiency was shown by the warm-up complex No. 2, lasting 22 minutes 40 seconds, consisting of 25% of physical exercises and 66.2% of digital ones, which includes the largest amount of physical exercises, compared with other complexes.